Дослідження методів кластеризації для реалізації рекомендаційної функції на основі сумісної фільтрації в системах перегляду фільмів - Касумов, Б. Р. (ХНУРЕ, 2025)
This work is devoted to the study of clusterization methods for implementing a recommendation function based on combined filtering in movie viewing systems. The article investigates five clustering methods k-means, DBSCAN and three modifications of DBSCAN: OPTICS, HDBSCAN and ST-DBSCAN. The test data was taken from the MovieLens platform and the software was developed in the Python programming language using the Anaconda platform.
Keywords: рекомендаційна функція; система фільтрації